W poszukiwaniu prawdy w naukach o kulturze - Rotengruber, Przemysław (Humaniora. Czasopismo Internetowe, 2019)
The question of the truth is of great importance for social sciences and humanities today. No matter how much they focus on the dynamics of changes in the human world, the criterion of their credibility is whether they can use reporting knowledge to predict the future. To pay off their debt, these sciences are looking for a tool that allows them, if not discovering the truth, then at least (gradually) approaching it. This task has two difficulties. First of all, what is the truth understood as the final product of science. Secondly, by what method its representatives can seek the truth about what cultural reality is? What form does it take in our time? This article is devoted to these considerations.